Peningkatan Citra Produk Menu Sarapan UMKM Dapoer Bolodewo melalui Strategi Branding dan Testimoni Konsumen - Shofiatun Nimah; Lintang Ayu Kusumastuti; Diah Ayu Kartika Sari; Siti Alliyah (Yayasan Literasi Sains Indonesia, 2025)
This community service program aims to enhance the product image of the Dapoer Bolodewo MSME, which operates in the culinary sector, specifically in packaged breakfast menus. The main problems faced include the absence of a strong brand identity, limited promotional media, and suboptimal hygiene standards in the production process. To address these challenges, a branding strategy was implemented through several stages: creating a logo and product labels, developing visual promotional media such as banners and signboards, utilizing Instagram to expand marketing reach, and providing aprons to business owners to support hygiene and professionalism. The entire activity was carried out using a participatory approach, where the service team worked closely with the MSME throughout the implementation process. The results of the program showed a significant improvement in brand recognition, consumer interest, and product sales. An integrated branding strategy-both visual and digital-proved effective in enhancing the competitiveness of MSMEs in a highly competitive local market. Moreover, the program demonstrated that collaboration between academic teams and entrepreneurs through active mentoring can effectively foster sustainable MSME growth. This empowerment model may serve as a reference and be replicated for other MSMEs facing similar challenges in developing a more professional and competitive business image.